Intraosseous xanthoma simultaneously treated with mandibular prognathism using sagittal split ramus osteotomy in the mandible: a case report and literature review - Lee, Yong Sun; Youn, Sung Bin; Choi, Sul Gi; Do, Kyung Lok; Namis, Sultan; Seo, Byoung-Moo (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2025)
Xanthomas are benign lesions characterized by the aggregation of lipid-laden histiocytes and foamy cells within tissues. Intraosseous xanthomas (IOXs), especially those in the jaw bone, are rare, with only around 50 cases documented. This case report describes an IOX located at an osteotomy site in the mandible during sagittal split ramus osteotomy (SSRO). Preoperative radiographs revealed a heterogenic radiolucent-radiopaque lesion in the right ramus. After meticulous curettage of the lesion, proximal and distal segments were fixed in the semi-rigid plates and screws. At the one-year followup, radiographs showed excellent bony union between proximal and distal segments, with no significant interval change. IOXs rarely occur in the jaw. However, their predilection for the posterior mandible suggests that such lesions can be encountered during orthognathic surgery. This report demonstrates the feasibility of performing SSRO directly through the lesion with concurrent curettage without compromising surgical outcomes. This case will contribute to the limited literature on IOX of the jaw bone and its treatment via SSRO as a feasible surgical option in concomitant orthognathic surgery.